Behind the Retraction Curve: Bibliometric Insights into Publication Integrity at India’s Top Ten NIRF-Ranked Research Institutions - Gayang, Fullstar Lamin; Islam, Akramul; Ravikumar, S.; Kharlukhi, Olivia; Dopri, Mejurishisha (Information Research Communications, 2026)
Scientific retractions are increasingly recognized as a critical indicator of research integrity, publication ethics, and institutional accountability. This study presents a bibliometric analysis of retracted documents indexed in Scopus from ten of India’s top-ranked research institutions as identified by the National Institutional Ranking Framework (NIRF) 2025, covering the period from 2000 to 2026. The institutions examined include the Indian Institute of Science (IISc), Indian Institutes of Technology (IIT) at Madras, Delhi, Bombay, Kharagpur, Kanpur, Roorkee, and Guwahati, the Academy of Scientific and Innovative Research (AcSIR), and the Homi Bhabha National Institute (HBNI). Bibliometric indicators including document counts, citation profiles, authorship patterns, international collaboration rates, and Bradford’s Law zone classifications were employed to assess the landscape of retracted scholarship across these institutions. Findings reveal heterogeneous retraction profiles, with IIT Roorkee recording the highest number of retracted documents and HBNI the lowest. Citation inflation prior to retraction, high international co-authorship in retracted papers, and disciplinary concentration in life sciences and materials research are among the key patterns identified. The collective retraction record across these ten institutions points to structural vulnerabilities in India's research ecosystem that warrant systematic policy intervention.
Keywords: Retraction; Research integrity; NIRF; Indian academia; Publication ethics